Folklore as a pedagogical tool: Enhancing cultural awareness in Shakespeare’s The Merchant of Venice - Uddin, Mohammad Jashim; Alam, K Ahmed; Talukder, Md Zakir Hossain (Journal of Interdisciplinary Studies in Education, 2025)
In this paper, we investigate the role of folklore as a pedagogical tool in enhancing cultural awareness and critical engagement through Shakespeare’s The Merchant of Venice. The study highlights how these motifs shape character motivations, thematic structures, and societal dynamics within the play by analyzing key folkloric elements such as myths, superstitions, and cultural narratives. Employing a qualitative methodology, the research explores the cultural tensions, prejudices, and values of the Renaissance period and examines their relevance to contemporary societal issues. Grounded in theoretical frameworks such as folklore theory, cultural pedagogy, and critical identity theory, the study demonstrates how integrating folklore into educational practices fosters empathy, critical thinking, and a nuanced understanding of cultural diversity. The findings reveal the transformative potential of folklore-based pedagogy in creating critically engaged learners and underline Shakespeare’s enduring value in addressing themes of prejudice, identity, and cultural inclusion.